Desempenho e Características de Carcaça de Bezerros Confinados Recebendo Dietas com Diferentes Degradabilidades da Fração Protéica - Cervieri, Rafael Da Costa [UNESP]; Arrigoni, Mário De Beni [UNESP]; De Oliveira, Henrique Nunes [UNESP]; Silveira, Antônio Carlos [UNESP]; Chardulo, Luis Arthur Loyola [UNESP]; Costa, Ciniro [UNESP]; Martins, Cyntia Ludovico [UNESP] (My University, 2001)
The objective of this study was to evaluate the effects of different levels of degradable intake protein (DIP) diets during the feedlot-growing phase, on performance, in vivo growth parameters measured by ultrasound and on carcass traits and meat quality of young bulls. Sixty Brangus calves, 8 months old, averaging 243,2 kg, were submitted to three treatments in growing (Phase 1) and finishing (Phase 2) phases: T1 - 69% DIP in Phases 1 and 2; T2 - 77% DIP in Phase 1 and 69% DIP in Phase 2; T3 - 61% DIP in Phase 1 and 69% DIP in Phase 2. In Phase 1, animals on treatments T2 showed a lower average daily gain than those on treatments T1 and worst feed conversion than T1 and T3 (P<.05). Hot carcass weight, dressing percentage, weights of the forequarter, plate and hindquarter, and the rib eye area, fat thickness, shear force and chemical composition did not statistically differ among treatments. Diets with less DIP improved feed conversion and average daily gain in 11.5 and 16.9%, respectively, during the growing phase, suggesting the use of lower levels of DIP during this period.
Performance and Carcass Traits of Feedlot Calves Receiving Diets with Different Degradabilities of the Protein Fraction
Keywords: Brangus; Carcass; Degradable intake protein; Young bulls